2010
DOI: 10.1158/1055-9965.epi-10-0036
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution from Traffic and Risk for Lung Cancer in Three Danish Cohorts

Abstract: Background: Air pollution is suspected to cause lung cancer. The purpose was to investigate whether the concentration of nitrogen oxides (NO x ) at the residence, used as an indicator of air pollution from traffic, is associated with risk for lung cancer.Methods: We identified 679 lung cancer cases in the Danish Cancer Registry from the members of three prospective cohorts and selected a comparison group of 3,481 persons from the same cohorts in a case-cohort design. Residential addresses from January 1, 1971,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 33 publications
2
57
3
Order By: Relevance
“…Furthermore, this misclassification was found to be a Berkson-type error, which is not expected to bias the estimates but likely decreases their precision, as discussed in more detail elsewhere. 35 Our study offers new evidence that long-term exposure to traffic-related air pollution in adult life may be a risk factor for ischemic stroke but not hemorrhagic stroke. Fatal ischemic strokes, likely denoting admissions for more severe strokes, were most strongly associated with NO 2 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, this misclassification was found to be a Berkson-type error, which is not expected to bias the estimates but likely decreases their precision, as discussed in more detail elsewhere. 35 Our study offers new evidence that long-term exposure to traffic-related air pollution in adult life may be a risk factor for ischemic stroke but not hemorrhagic stroke. Fatal ischemic strokes, likely denoting admissions for more severe strokes, were most strongly associated with NO 2 .…”
Section: Discussionmentioning
confidence: 67%
“…The dispersion models used to assess NO 2 levels have been successfully validated against measured values 33 (see details in an online Supplemental material) and applied earlier in studies of chronic obstructive pulmonary disease 34 and lung cancer 35 in this cohort. A limitation of the exposure assessment method is that we assessed only outdoor concentrations and lacked information on work address, commuting habits, and personal activities.…”
Section: Discussionmentioning
confidence: 99%
“…We performed Pearson correlation for normal and Spearman correlation for non-normal data. However, most studies that tested the delayed health effects of contaminants observed the effects in delays of a few days and less than a month [20,21]. Therefore, in this study we only examined the correlation of onemonth delay with cardiovascular deaths.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…18 Yet the epidemiological explanation of this phenomenon is still insufficient. Some studies have found excess cancer mortality associated with higher doses of exposure to carcinogens in the urban environment, such as air pollution 8,19,20 and estrogenic compounds. 21,22 The major behavioral risk factors for cancer are known to be tobacco, alcohol, and diet and physical activity, 23 but there is still a lack of substantial epidemiological evidence that exposure to these risks or the causal effects of these risks are aggravated in urban areas.…”
Section: Discussionmentioning
confidence: 99%